The The Mediation Effect of Market Performance on the Effect of Capital Intensity Ratio, Inventory Intensity Ratio, Managerial Ownership, and Institutional Ownership on Tax Aggressiveness - Handayani, Rini; Carolina, Verani; Amanda, Verna Budi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
This study aims to analyze the mediating effect of Market Performance on the influence of Capital Intensity Ratio, Inventory Intensity Ratio, and Ownership Structure on Tax Aggressiveness Study on Manufacturing Companies Listed on the Indonesia Stock Exchange (ISE) for the period 2015-2019. The population used in this study is all companies listed on the ISE, and the sample used in this study is manufacturing companies listed on the ISE from 2015 to 2019. The testing method used in this study is Path Analysis. Based on the results of the tests carried out using SPSS, the results show that there is an effect of Capital Intensity Ratio, Inventory Intensity Ratio, Managerial Ownership, and Institutional Ownership on Tax Aggressiveness mediated by Market Performance, but overall the magnitude of the direct influence test of Capital Intensity Ratio, Inventory Intensity Ratio, Managerial Ownership, and Institutional Ownership on Tax Aggressiveness is greater than if using the Market Performance variable as a mediating variable.